2018
DOI: 10.3390/diagnostics9010002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transabdominal Ultrasound in the Diagnosis of Early Stage Pancreatic Cancer: Review and Single-Center Experience

Abstract: Pancreatic cancer (PC) is the fourth leading cause of cancer-related death with a 5-year survival rate less than 10%. In the absence of effective screening methods, such as blood markers, most clinical diagnoses of PC are made at an advanced stage. However, early stage PC is associated with a more favorable five-year survival rate of 85.8% for stage 0, and 68.7% for stage IA. Transabdominal ultrasound (US) is frequently used as a first-line diagnostic tool in the clinical setting and a preferred modality for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…Less expensive, short-protocol MRI has been evaluated for cyst surveillance 67. Some Japanese centres have evaluated abdominal ultrasound as a screening modality,68 as detailed pancreas sonographic images are feasible in thin individuals, but there was consensus that abdominal ultrasound should not be a first-line test for pancreatic surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…Less expensive, short-protocol MRI has been evaluated for cyst surveillance 67. Some Japanese centres have evaluated abdominal ultrasound as a screening modality,68 as detailed pancreas sonographic images are feasible in thin individuals, but there was consensus that abdominal ultrasound should not be a first-line test for pancreatic surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…Transabdominal ultrasound (US) is an imaging modality that allows non-invasive observation of abdominal organs. The reported sensitivity and specificity of transabdominal US for the detection of pancreatic cancer range from 75% to 89% and 90% to 99%, respectively [ 113 , 114 ]. Recently, Kanno et al reported the results of a multi-center retrospective study of 200 cases of early stage pancreatic cancer, including 51 cases of stage 0 and 149 cases of stage I disease [ 115 ].…”
Section: Possible Non-invasive Imaging Modalities For Early Detectmentioning
confidence: 99%
“…Its sensitivity for the detection of PC is approximately 75–89% [ 9 ], and its capability to detect PC is reduced by obesity or the presence of gastric gas [ 10 ]. To overcome these disadvantages of conventional US, we developed a special US examination focusing on the pancreas (hereafter referred to as special pancreatic US) [ 8 , 10 , 11 , 12 , 13 , 14 ]. Special pancreatic US is performed in the sitting position following the ingestion of liquid to reduce the effect of gastric gas [ 10 ].…”
Section: Introductionmentioning
confidence: 99%